USE OF CLOUD TECHNOLOGIES IN THE DEVELOPMENT OF TEACHERS INFORMATION COMPETENCES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the benefits of using cloud technology in education.